WID approach in teaching research writing to engineering postgraduate students - Elena I. Shpit (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Academic (research) writing in the English language is a key professional skill, in particular, in engineering sciences. However, most Russian-speaking researchers have challenges in choosing rhetoric that would comply with the norms and traditions of a disciplinary discourse community. Therefore, the most relevant approach in teaching research writing to postgraduate students is «writing in the discipline» (WID) that focuses on the rhetoric conventions of a discipline. In this paper, we present the experience of using the results and implications of the analyses of scientific-engineering discourse in teaching research writing to postgraduate engineering students and the verification of the efficiency of such teaching experience. To verify the efficiency, we employed the comparative analysis of two types of writing: of international researchers and of postgraduates who completed the course. The results show that, postgraduate writing does not differ from the writing of international researchers in 20 out of 41 text features and demonstrate a successful acquisition of the new knowledge and skills, especially from the zone of proximal development. However, the remaining features illustrate considerable difference between the two types of writing. The totality of possible reasons proves the complexity of the research writing phenomenon and implies that the improvement of disciplinary skills in academic writing require continuous and systematic practice not only in the postgraduate program but throughout the university studies as well.